ANALYSIS OF SOCIAL MEDIA’S ACCESS; RELATION TO CHARACTER OF VOCATIONAL STUDENT IN BOGOR - Rahmawati, Sudi Herlin; Hastuti, Dwi; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2014)
Recently, the existence of social media in Indonesia is consequence of acculturation both of culture and technology. This study aimed to analyze the relation of social media on the teenagers’ character development, particularly responsibility, respectful, and courtesy. The observation was conducted in two vocational private high schools in Bogor, West Java Province. The selected schools were chosen as schools with high involvement on juvenile delinquency such as gang fight, drugs, and free-sex based on the data from local government official. Total participants were 100 students consist of 50 male and 50 female students at 1st and 2nd grade. Based on the analysis, there was significant difference between male and female student on accessing the social media (both on intensity and content). Females’ scored higher than male in accessing Facebook, Twitter, YouTube, etc. On average, females’ use of social media was between 2-3 hours per day, whereas for male it was only 1 hour. However, male had greater access to pornography than the females. The study found significant correlation between media social intensity and content access with the character. Highly teenagers’ access to social media; correlate with the low of responsibility, respectful and courtesy character.